2023
DOI: 10.3389/fimmu.2023.1200180
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of cell therapy for COVID-19: global clinical trial landscape, published safety/efficacy outcomes, cell product manufacturing and clinical delivery

Abstract: During the pandemic of severe respiratory distress syndrome coronavirus 2 (SARS-CoV2), many novel therapeutic modalities to treat Coronavirus 2019 induced disease (COVID-19) were explored. This study summarizes 195 clinical trials of advanced cell therapies targeting COVID-19 that were registered over the two years between January 2020 to December 2021. In addition, this work also analyzed the cell manufacturing and clinical delivery experience of 26 trials that published their outcomes by July 2022. Our demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Therapies focused on preventing secondary damage post injury and suppressing a dysregulated immune response will serve to improve patient outcomes. Although treating coagulopathic patients with pro-coagulant MSCs must be approached with caution ( 16 , 19 , 20 , 103 ), MSCs’ immunomodulation potential suggests that their use in any population such as trauma patients who are susceptible to a hyperactive immune response and coagulopathy ( 110 ) may be beneficial. It is hoped that these short-term assays will aid in developing, screening, and customizing cell therapy for the aid of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapies focused on preventing secondary damage post injury and suppressing a dysregulated immune response will serve to improve patient outcomes. Although treating coagulopathic patients with pro-coagulant MSCs must be approached with caution ( 16 , 19 , 20 , 103 ), MSCs’ immunomodulation potential suggests that their use in any population such as trauma patients who are susceptible to a hyperactive immune response and coagulopathy ( 110 ) may be beneficial. It is hoped that these short-term assays will aid in developing, screening, and customizing cell therapy for the aid of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Their potential was also recently realized in several COVID therapies (12)(13)(14)(15). The most comprehensive and up-to-date summary on the use of MSCs for COVID19 was recently published by Couto et al in Frontiers Immunology 2023 (16).…”
Section: Background and Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the clinical trials using UC-MSCs introduced in Tables 1 and 2 , there are accumulating early-phase clinical trials using UC-MSCs [ 17 , 20 , 23 , 33 35 ] for engraftment facilitation in HSCT for aplastic anemia [ 36 ], neurogenic injuries, diabetes mellitus (DM), heart and angioplasty, liver damage including liver cirrhosis, inflammatory bowel diseases such as Crohn’s disease and ulcerative colitis, prevention of acute rejection in renal transplantation, and collagen diseases [ 33 ]. The number of relevant clinical trials on the NIH clinical trial website ( https://00m.in/HHVJP ) has increased up to 95 trials, including complete, recruiting, and not-yet-recruiting status, as of the end of May 2023.…”
Section: Cb and Uc For Exploring New Cell Modalitiesmentioning
confidence: 99%
“…After establishing the functional role of RABs directed against the angiotensin II type 1 receptor (AT1R) and endothelin receptor type A (ETAR) for vascular integrity and graft function/survival in the KTx setting ( 4 , 8 , 9 , 11 16 ), subsequent studies have identified several RABs directed against GPCR targets typically associated with the vasculature, such as protease-activated receptors (PARs), neuronal and chemokine receptors, and the levels of these RABs are often modulated with patient age and disease status ( 1 , 17 , 18 ). Vasculature-associated RAB targets can be found on different types of micro-/macro-vascular endothelial cells (ECs), vascular smooth muscle cells (VSCMs), and perivascular multipotent mesenchymal stromal/stem cells (MSCs), but also neuronal cells, which are all often employed as model systems to study respective molecular signaling mechanisms ( 1 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%